"Inhabitant’s knowledge" in the contemporary city: neighborhood narratives of a collaborative ethnography - Álvarez Pedrosian, Eduardo (Mediaciones Sociales, 2018)
In this paper, we presents the results of a work experience based on collaborative ethnography in a contemporary urban environment, on historic second enlargement of Montevideo city. We focus on what we call inhabitants knowledge, by to the analysis of productions of participants. First we present the general subject of the exploration of the city together. In second step, we advance on the analysis considering the collaborative learning since the ethnographic subjectivation. Then we expose each of the cases of the considered in this experience. We conclude characterized this knowledge and reconsidering the general aspects about urban mediations.